Intra- and inter-rater objectivity of the frequency speed of kick test - Antonaccio, R. F.; Machado, F. S. M.; da Silva Santos, J. F. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Aim. The purpose of this study was to investigate the frequency speed of kick test (FSKT) objectivity intra- and inter-rater. Material, Methods and Results. Two evaluators determined the performance during FSKT of fourteen taekwondo athletes. Each athlete performed the 10s version of the FSKT (FSKT10s) and five sets of 10s with 10s intervals (FSKTmult). The performance was recorded and analyzed posteriorly. Each evaluator analyzed the performance with one-week rest interval between them. This procedure was used to investigate intra-rater objectivity. The first count conducted by each evaluator was used to determine the inter-rater objectivity. The results obtained for intra- and inter-rater were classified as high (above 0.90) to all variables of the FSKT and low coefficient of variation (0%). Conclusions. The FSKT presented high intra- and inter-rater objectivity and can be applied by coaches to monitor sport-specific performance.